2014
DOI: 10.1088/1741-2560/11/5/051001
|View full text |Cite
|
Sign up to set email alerts
|

The role of muscle synergies in myoelectric control: trends and challenges for simultaneous multifunction control

Abstract: Myoelectric control is filled with potential to significantly change human-robot interaction due to the ability to non-invasively measure human motion intent. However, current control schemes have struggled to achieve the robust performance that is necessary for use in commercial applications. As demands in myoelectric control trend toward simultaneous multifunctional control, multi-muscle coordinations, or synergies, play larger roles in the success of the control scheme. Detecting and refining patterns in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
107
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(112 citation statements)
references
References 260 publications
3
107
0
2
Order By: Relevance
“…"EMG features extract structural characteristics from a single channel to describe the specific signal [5]." The features of muscle synergy are time-invariant, containing information from multiple EMG channels that can depict the underlying muscle coordination principles while performing various motions [5]. Root mean square (RMS) is selected as the EMG feature from the datasets.…”
Section: Ninapro Databasementioning
confidence: 99%
See 2 more Smart Citations
“…"EMG features extract structural characteristics from a single channel to describe the specific signal [5]." The features of muscle synergy are time-invariant, containing information from multiple EMG channels that can depict the underlying muscle coordination principles while performing various motions [5]. Root mean square (RMS) is selected as the EMG feature from the datasets.…”
Section: Ninapro Databasementioning
confidence: 99%
“…Myoelectric control started to gain attention as a feature control mechanism in the 1940s [5]. It has the potential to lead a revolution in human-machine interaction due to its ability to measure human motion intention [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the dynamic motion such as jumping and running, the multichannel sEMG signals vary greatly with time which may result in high risk for overfitting models to training data and frequent retraining [21]. Moreover, for the application of exoskeletons, myoelectric prostheses, and rehabilitation gait, it is always desirable to generate selfadapted gait with limited experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The author has extensive research back-ground on BMIs using electromyography (EMG) signals from upper limb muscles [8][9][10][11][12][13][14][15][16][17][18][19], and neural recordings [20,21]. We recently proposed that instead of using the decoder-based technique for BMIs, human subjects can learn to map their neural activity into control actions for an artificial system [22][23][24][25][26][27][28]. More specifically we have shown that subjects can control artificial systems using muscular activation, without requiring a decoding function to map one to the other.…”
Section: Background and Introductionmentioning
confidence: 99%